Solitary Wave Solutions of Conformable Time Fractional Equations Using Modified Simplest Equation Method - Waseem Razzaq; Mustafa Habib; Muhammad Nadeem; Asim Zafar; Ilyas Khan; Patrick Kandege Mwanakatwea (Complexity)
This study presents a modified simplest equation method (MSEM) to investigate some real and exact solutions of conformable time fractional Benjamin-Bona-Mahony (BBM) equation and Chan-Hilliard (CH) equation. We use traveling wave transformation to obtain the results in the form of series solution. Some calculations are performed through Mathematica software to analyze the accuracy of this approach. Graphical representations are reported for more significant results at different fractional-order which demonstrates that this approach is very simple, adequate, and legitimate.